Case report: Post-therapeutic laryngeal carcinoma patient possessing a high ratio of aneuploid CTECs to CTCs rapidly developed de novo malignancy in pancreas - Mi, Jiaoping; Yang, Fang; Liu, Jiani; Liu, Mingyang; Lin, Alexander Y.; Wang, Daisy Dandan; Lin, Peter Ping; Zeng, Qi (Frontiers in Oncology, 2022)
Effectively evaluating therapeutic efficacy, detecting minimal residual disease (MRD) after therapy completion, and predicting early occurrence of malignancy in cancer patients remain as unmet imperative clinical demands. This article presents a case of a laryngeal carcinoma patient who had a surgical resection and complete post-operative chemoradiotherapy in combination with the targeted therapy, then rapidly developed pancreatic adenocarcinoma. Detected by SE-iFISH, the patient had a substantial amount of 107 non-hematological aneuploid circulating rare cells including 14 circulating tumor cells (CTCs, CD31-/CD45-) and 93 circulating tumor endothelial cells (CTECs, CD31+/CD45-) with a high ratio of CTECs/CTCs > 5 upon finishing post-surgical combination regimens. Positive detection of those aneuploid non-hematological circulating rare cells was five months prior to subsequent plasma CA19-9 increasing and ten months before the de novo pancreatic cancer was diagnosed by medical imaging modalities. Besides previously reported clinical utilities of co-detection of aneuploid CD31- CTCs and CD31+ CTECs in real-time evaluation of therapeutic efficacy, longitudinal monitoring of emerging treatment resistance and adequate detection of MRD, a large cohort study is necessary to further investigate whether, and how, a high ratio of MRD CTECs to CTCs may function as an appropriate index forecasting either occurrence or metastatic distant recurrence of malignancy in post-therapeutic cancer patients.